Diagnosis and management of invasive fungal diseases in non-neutropenic ICU patients, with focus on candidiasis and aspergillosis: a comprehensive review - Azim, Afzal; Ahmed, Armin (Frontiers in Cellular and Infection Microbiology, 2024)
Invasive fungal diseases pose a significant threat to non-neutropenic ICU patients, with Candida and Aspergillus infections being the most common. However, diagnosing these infections in the ICU population remains challenging due to overlapping clinical features, poor sensitivity of blood cultures, and invasive sampling requirements. The classical host criteria for defining invasive fungal disease do not fully apply to ICU patients, leading to missed or delayed diagnoses. Recent advancements have improved our understanding of invasive fungal diseases, leading to revised definitions and diagnostic criteria. However, the diagnostic difficulties in ICU patients remain unresolved, highlighting the need for further research and evidence generation. Invasive candidiasis is the most prevalent form of invasive fungal disease in non-neutropenic ICU patients, presenting as candidemia and deep-seated candidiasis. Diagnosis relies on positive blood cultures or histopathology, while non-culture-based techniques such as beta-D-glucan assay and PCR-based tests show promise. Invasive aspergillosis predominantly manifests as invasive pulmonary aspergillosis in ICU patients, often associated with comorbidities and respiratory deterioration in viral pneumonia. Diagnosis remains challenging due to poor sensitivity of blood cultures and difficulties in performing lung biopsies. Various diagnostic criteria have been proposed, including mycological evidence, clinical/radiological factors and expanded list of host factors. Non-culture-based techniques such as galactomannan assay and PCR-based tests can aid in diagnosis. Antifungal management involves tailored therapy based on guidelines and individual patient factors. The complexity of diagnosing and managing invasive fungal diseases in ICU patients underscore the importance of ongoing research and the need for updated diagnostic criteria and treatment approaches. Invasive fungal disease, Invasive fungal infection, Invasive candidiasis, Invasive aspergillosis, Antifungal drugs.